The Clinical Characteristics of Patients with Embolic Strokes among Indonesian Subjects - Syahrul; Imran; Farida; Suherman; Nasrul Musadir; Nurul Fajri; Endang Mutiawati; Nova Dian Lestari (Britain International for Academic Research (BIAR) Publisher, 2020)
Stroke accounts for 10% of the world's deaths and causes severe long-term disabilities. Twenty-six million people world wide experience a stroke each year. Two-thirds represents cerebral ischemia. Age, a history of stroke or transient ischemic attack, hypertension, diabetes and heart failure characterize a stroke. Early detection with a proper treatment could improve clinical outcomes in such cases.